Pengaruh Media Pembelajaran Audio Visual Terhadap Hasil Belajar Geografi Siswa Kelas X - Ferdrika Bobii; Yuli Ifana Sari; Siti Halimatus Sakdiyah (Geography Education Study Program, Universitas Kanjuruhan Malang, 2025)
This study aims to determine the effect of audio-visual learning media on the geography learning outcomes of tenth-grade students at SMA Negeri 6 Malang. The research employed a quasi-experimental method with a Nonequivalent Control Group Design, involving one experimental class (X-3) and one control class (X-4), each consisting of 35 students. The research instrument was an essay test comprising five questions that had been tested for validity, reliability, difficulty level, and discriminating power. Data were collected through essay tests, observation, and documentation, and analyzed using the t-test. The results showed a significant difference in learning outcomes between students taught using audio-visual media and those taught through conventional methods. The post-test average score of the experimental class was higher than that of the control class, with a greater gain score improvement. These findings demonstrate that audio-visual media can effectively enhance students’ motivation, engagement, and understanding of geography material, particularly in the topic of maps. The study suggests that teachers should optimally integrate audio-visual media into geography instruction to create engaging, interactive, and effective learning experiences that improve student achievement.